2016
DOI: 10.1158/1541-7786.mcr-15-0363
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of DNA Damage Checkpoint Signaling Contributes to Mutant p53 Accumulation via Modulation of p53 Ubiquitination

Abstract: Many mutant p53 proteins exhibit an abnormally long half-life and overall increased abundance compared to wild-type p53 in tumors, contributing to mutant p53’s gain-of-function oncogenic properties. Here a novel mechanism is revealed for the maintenance of mutant p53 abundance in cancer that is dependent on DNA damage checkpoint activation. High level mutant p53 expression in lung cancer cells was associated with preferential p53 mono vs. polyubiquitination, suggesting a role for the ubiquitin/proteasome syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…However, a twofold higher uptake of irinotecan was reported in HT29 cells than in LoVo cells regardless of the ABCG2 transporter, indicating that the difference in the sensitivity to irinotecan could be because of the cellular accumulation of this drug . In addition, this study supports the idea that cells with higher mutp53 levels are those with more active DNA damage signaling as reported earlier . DNA damage due to irinotecan triggered the phosphorylation of H2AX concurrently with the activation of Chk2 and p53 in mutp53 HT29 cells and, to a much lesser degree, in wtp53 HCT116 cells because of the lack of resolution of damage arising from the loss of p53 function.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, a twofold higher uptake of irinotecan was reported in HT29 cells than in LoVo cells regardless of the ABCG2 transporter, indicating that the difference in the sensitivity to irinotecan could be because of the cellular accumulation of this drug . In addition, this study supports the idea that cells with higher mutp53 levels are those with more active DNA damage signaling as reported earlier . DNA damage due to irinotecan triggered the phosphorylation of H2AX concurrently with the activation of Chk2 and p53 in mutp53 HT29 cells and, to a much lesser degree, in wtp53 HCT116 cells because of the lack of resolution of damage arising from the loss of p53 function.…”
Section: Discussionsupporting
confidence: 87%
“…49 In addition, this study supports the idea that cells with higher mutp53 levels are those with more active DNA damage signaling as reported earlier. 52 DNA damage due to irinotecan triggered the phosphorylation of H2AX concurrently with the activation of Chk2 and p53 in mutp53 HT29 cells and, to a much lesser degree, in wtp53 HCT116 cells because of the lack of resolution of damage arising from the loss of p53 function. Although the A452irinotecan combination did not trigger the synergistic effect on DNA damage checkpoint and p53 activation, it led to synergistically increase the accumulation of γH2AX in HT29 cells, indicating that the combination markedly blocks to repair DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…ROS plays an important role in cell signaling, intracellular redox status changes and cell death. It is evident that tumor suppressor gene p53 is induced by DNA damage 11 . It has been demonstrated that phosphorylation and dephosphorylation of some regulatory proteins play crucial role in controlling cell growth and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…This activation is known to arrest cells at a specific phase of the cell cycle, which may provide time to repair of damage and recovery of cells. Activation of the checkpoint is regulated by damage sensors, namely ATM and ATR 11,16 . These kinases phosphorylate downstream targets in signal transduction cascade, eventually leading to cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…17 Cell autonomous pathways were also considered with regard to continuous DNA repair signaling; it was discovered that prolonged engagement of the DNA repair checkpoint facilitates enrichment of mutant p53. 18 Epigenetic alterations resulting from metabolic reprogramming in cancer cells were observed to promote DNA repair and thereby enhance cell survival, adding strength to the concept that cross-talk between DNA repair and metabolic pathways may affect cancer phenotypes. The role of miRNAs was assessed; using unbiased screening in glioblastoma cells identified four miRNAs that promote radioresistance and connect regulation to TGF-B.…”
mentioning
confidence: 99%